Inventory management proposal: a case study in a pharmacy in eastern Minas Gerais - Souza, Cintia Couto de; Longhini, Tatielle Menolli (Brazilian Journal of Production Engineering, 2025)
The performance of an inventory management system is essential to ensure good results. This is because the principles, methods and techniques of inventory control ensure the optimization of investments and the minimization of total costs. This work is the result of a study developed in a drugstore located in the city of Governador Valadares - MG, where a formal and standardized method of inventory management was not identified. After this identification, a dynamic and functional management model was suggested, with the application of easy-to-use tools. The work is characterized as a case study that proposes an inventory management model based on inventory policies and demand forecasting. As a control tool, the ABC classification was adopted to identify the level of importance of medicines in the drugstore. After this recognition, inventory policies were suggested for items categorized in class A, as they represent important assets for the enterprise. An analysis of demand behavior was also performed, in order to subsequently propose an appropriate forecasting model. Among the models studied, it was found that the forecasting methods by exponential moving average and simple seasonality presented the best results. Finally, it was possible to develop inventory policies to balance supply and demand, keeping the appropriate quantity of items in stock, that is, without shortages or excesses.
Keywords: Inventory; ABC Classification; Demand; Inventory Policies.